The Tsunami Disaster in Asia - Unahlekhaka, Akeau; Mehta, Geeta (International Journal of Infection Control, 2009)
On December 26, 2004, a devastating tsunami arising from an earthquake which had its epicentre near Indonesia in the Indian Ocean attacked many countries along the Indian Ocean: India, Indonesia, Malaysia, Maldives, Seychelles, Somalia, Sri Lanka and Thailand. The tsunami resulted in more casualties than any in history. As of mid-February, 2005, an estimated 214,000 people were dead, 142,000 reported missing, and more than 3,400 injured. A natural phenomenon, tsunamis are giant sea waves caused by a submarine earthquake or slope collapse into the sea bed. The giant sea waves reach the coast after traveling thousands of miles at speeds of 300-600 mph and making inroads at great force into the shoreline. Waves lash out at built structures, plants, trees and human habitations causing massive flooding and destruction.